Sports and Psychology Curriculum Development Processes and Reforms of Singapore, Ireland, Finland, Turkey, and Hong Kong - E. Seda KOÇ (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The administration faces a hurdle in curriculum building while anticipating the future needs of the pupils. The industrialized nations have the proper system for curriculum development required for students' sustainable learning. There is a lack of emphasis on curriculum development in sports and psychology. This study examines the sports and psychology curriculum development and reform processes in Singapore, Ireland, Finland, Turkey and Hong Kong. This research is based on secondary data and makes use of document analysis. The findings indicate that countries, including Turkey, should prioritize the development of sports and psychological curricula for the optimal development and education of pupils. The study is based on a novel concept that examines the considerable knowledge gap regarding the creation and reform of sports and psychology curricula. Theoretically, this research is very significant because it has explored the sports and psychology curriculum development process and reforms. This research has addressed the practical challenges of the curriculum creation process and changes in Singapore, Ireland, Turkey, Finland, and Hong Kong, making it valuable from a practical standpoint. Future scholarly works that wish to make a substantial contribution to the body of literature are encouraged to follow the future directions advised by the research.